APLIKASI E-LEARNING MATA PELAJARAN AQIDAH AHLAK PADA MADRASAH TSANAWIYAH MUHAMMADIYAH ISIMU GORONTALO BERBASIS ANDROID - irfan abbas (Jurnal Informatika Upgris, 2018)
ABSTRACTMadrasah Tsanawiyah (MTS) is a level of basic education in formal education in Indonesia which is held within 3 years. School students or madrasah students are generally 13-15 years old. Madrasah schools are a transition period from childhood to the world of adolescence. The period of MTS is a critical period for student education because at this time the transition from childhood. At present education is very much influenced by technological developments that provide a variety of conveniences so that it influences students' thinking, so schools must start working hard and pay attention to the education programs and methods used in transferring knowledge from teaching staff to students. The use of electronic circuits allows learning to be carried out in one place or in different places through distance learning. E-learning can be carried out anytime anywhere, but e-learning still has drawbacks, which requires users to deal with electronic equipment that is not flexible to move places. Mobile phones today are not only used as communication tools but can be used in finding information. One of the current operating systems that can access information very quickly and most in demand by the public today is Android. Android is an open source-based system that allows sources code (source code) on android to be read by development to customize various application features according to their usage needs. Mobile learning can be used as an alternative to solving problems in the field of education, especially the problem of equitable access to educational information, the quality of learning content in the form of learning material in the form of text or images accompanied by examples of teacher improvement questions to make or deliver learning materials and managing teaching andlearningactivities. Keywords: Madrasah Tsanawiyah (MTS), E-learning, Mobile learning, Android